Gestão democrática na educação do campo : o significado do projeto político pedagógico na construção de ações e relações participativas - Silva, Iorim Rodrigues da (2014)
This research linked to the Graduate Program in Education ( PPGEDU / CUR / UFMT ) in Teacher Training and Educational Public Policy, has as its object of study the school management in rural education: the meaning of the political pedagogic project in building the Democratic Management of the School. The overall objective was to analyze the understanding that teachers have about the meaning of the construction of the political pedagogic project process as a condition of building stock and participatory relationships within the school. To reach the goal, we adopted the interpretive qualitative approach, and the data collection was done through documentary analysis and questionnaire. The locus that enabled this study comprises a field school in the county Rondonópolis MT - taking as subjects six educators. To support the discussions in a critical perspective we take as basic education authors: Severino (1998 and 2006 ) ; Haddad (2012 ); Time ( 2007); Lück (1996 and 1998) and Oliveira ( 2005, 2007 ) . Conceptions of democratic management , its democratizing elements and organization of the Field Education were guided by reading authors such as Freire (1988 , 1997 , 2006) ; Arroyo ( 2005, 2006 ) ; Caldart (2004); Carvalho ( 2005, 2006 ) ; Garske ( 1998, 2000 , 2006) ; Gohn (2003 ) ; Paro (1993 , 1996, 2002 and 2004 ) ; Sander (1995 , 2005 and 2007. Was found in this study that teachers realize the importance of PPP to the democratization of management, but there is no consolidation of practices of effective participation of stakeholders in the school community which contributes significantly for autonomy and for consolidating more democratic management. Believe that this study will contribute to the evaluation of public policies for rural education, so that the school's role be reconsidered and that the PPP should be constituted in practice as a tool that strengthens democracy with the participation of all.